Micronutrients Intake and Central Obesity Associated with Blood Pressure in The Elderly in The Region of Jasinga District West Bogor - Irna Aprianti; Adhila Fayasari (Jurnal Dunia Gizi, 2021)
Introduction: The elderly are at risk for hypertension due to several dominant factors including being overweight, food intake, coffee drinking habits and heredity factors. Objective: To analyze the relationship between micronutrient intake and central obesity with blood pressure in the elderly in the district of Jasinga, West Bogor. Materials and Methods: This type of research used a cross sectional design involving 68 elderly respondents. Bivariate analysis related to micronutrient intake (sodium, potassium, and magnesium) and central obesity using chi square analysis. Results: The results of statistical analysis showed that there was a relationship between sodium intake and systolic and diastolic blood pressure (p 0.05) in the elderly, there is a relationship between potassium intake and systolic and diastolic blood pressure (p 0.05) in the elderly, there is no relationship between magnesium intake and systolic and diastolic blood pressure (p 0.05) in the elderly, and there is a relationship between central obesity and systolic blood pressure and and diastolic (p 0.05) in the elderly. Conclusion: It can be concluded that there is a relationship between intake of sodium, potassium and central obesity with blood pressure in the elderly. There is no relationship between magnesium intake and blood pressure in the elderly.